2015
DOI: 10.1016/j.pnsc.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Hot deformation behavior of 51.1Zr–40.2Ti–4.5Al–4.2V alloy in the single β phase field

Abstract: The hot deformation behavior of a newly developed 51.1Zr-40.2Ti-4.5Al-4.2 V alloy was investigated by compression tests in the deformation temperature range from 800 to 1050 1C and strain rate range from 10 À 3 to 10 0 s À 1 . At low temperatures and high strain rates, the flow curves exhibited a pronounced stress drop at the very beginning of deformation, followed by a slow decrease in flow stress with increasing strain. The magnitude of the stress drop increased with decreasing deformation temperature and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…This leads to higher strain hardening. At higher temperatures (450 o C and 500 o C), the material became more ductile and has a softening behavior [33]. It can be concluded that the flow stress is directly dependent on the strain rate.…”
Section: Flow Stress-strain Investigationmentioning
confidence: 96%
“…This leads to higher strain hardening. At higher temperatures (450 o C and 500 o C), the material became more ductile and has a softening behavior [33]. It can be concluded that the flow stress is directly dependent on the strain rate.…”
Section: Flow Stress-strain Investigationmentioning
confidence: 96%